Happy narwhalidays - Clanton, Ben, 1988- ([Toronto, Ontario] : Tundra Books, 2020)
Narwhal and Jelly celebrate their favorite time of the year.
'Tis the season -- Cool facts -- The perfect present -- The mean green jelly bean -- The Merry Mermicorn! -- The Merry Mermicorn song!
2.0.
K-3.
GN550L
Keywords: Friendship -- Comic books, strips, etc -- Juvenile fiction; Narwhal -- Comic books, strips, etc -- Juvenile fiction; Jellyfishes -- Comic books, strips, etc -- Juvenile fiction; Marine animals -- Comic books, strips, etc -- Juvenile fiction; Ocean -- Comic books, strips, etc -- Juvenile fiction; Friendship -- Fiction; Narwhal -- Fiction; Jellyfishes -- Fiction; Marine animals -- Fiction; Ocean -- Fiction; Cartoons and comics; Humorous comics; Graphic novels; Comics (Graphic works); Christmas -- Fiction